The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/1678-457x.28716
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nutritional factors and digestibility of protein in Cayocar brasiliense seeds

Abstract: The Brazilian Cerrado presents a wide variety of natural products, including the Pequi (Caryocar brasiliense). The important factor that determines the dietary and nutritional ideality of protein is degestitibility. This work aims to evaluate the protein digestibility of Pequi seeds and the presence of anti-nutritional factors. The protein Pequi almonds were extracted, toasted and untoasted. Evaluation digestibility was structurally characterized by SDS-PAGE 15%, which can be used to analyze simulated gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the in vitro digestion simulation experiment of the Zihua snap bean lectin was studied. SDS–PAGE has been widely used in simulated gastric fluid (SGF) analysis and simulated intestinal fluid (SIF) analysis [45]. SDS–PAGE analyses of native lectin from the Zihua snap bean in SGF and SIF are shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the in vitro digestion simulation experiment of the Zihua snap bean lectin was studied. SDS–PAGE has been widely used in simulated gastric fluid (SGF) analysis and simulated intestinal fluid (SIF) analysis [45]. SDS–PAGE analyses of native lectin from the Zihua snap bean in SGF and SIF are shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…Hossain;Becker (2001) report the presence of these antinutritional factors in S. aculeata, S. rostrata and S. sesban seeds, but its contents are very low. Although, when isolated, these antinutritional factors have biological relevance, its absence in S. virgata seed is an interesting finding, because lectins and trypsin inhibitors generally do not degrade easily in the gastrointestinal tract and can be complexed with digestive enzymes, interfering in the nutrient absorption (SILVESTRINI et al, 2017). Additionally, the acceptability and use of legumes seeds have been affected by the presence of these antinutritional factors, which reduce the bioavailability nutrients (SHARAN et al, 2021).…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…Previous studies showed that Burkina Faso cowpea cultivars are rich in mineral elements (Fe, Zn, Mg, Ca, Se, K, Na), phenolic compounds and have significant antioxidant and anti-lipid peroxidation activities [5,6]. Legumes also contain antinutritional factors like saponin, heamaglutinin, cyanogenic glycoside, phytic acid, tannin, trypsin and chymotrypsin inhibitors that may reduce the bioavailability of nutrients and also cause harmful effects to human health [7,8]. Storage organs of plant such as seeds, tubers and also leaves, flowers, and fruits contain different types of protease inhibitors (PIs) which is able to inhibit some enzymes like trypsin, pepsin and chymotrypsin [9,10,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Legumes also contain antinutritional factors like saponin, heamaglutinin, cyanogenic glycoside, phytic acid, tannin, trypsin and chymotrypsin inhibitors that may reduce the bioavailability of nutrients and also cause harmful effects to human health [7,8]. Storage organs of plant such as seeds, tubers and also leaves, flowers, and fruits contain different types of protease inhibitors (PIs) which is able to inhibit some enzymes like trypsin, pepsin and chymotrypsin [9,10,7,11]. PIs are small proteins or peptides that inhibit the catalytic action of proteases by forming stoichiometric and stable complexes with their proteolytic enzymes blocking or altering the active site [11][12][13].…”
Section: Introductionmentioning
confidence: 99%